Electroconvulsive therapy for Depression in Anorexia Nervosa. A review - F. Azevedo; R. André; I. Donas-Boto; D. Jeremias; C. Almeida (European Psychiatry, 2022)
Introduction Anorexia nervosa has an important burden on both patients and families, with important comorbidities such as depression and obsessive symptoms. These are more resistant to pharmacological treatment than in non-anorexia patients, due to both biological and psychological mechanisms. Electroconvulsive therapy is the best available therapy for treatment resistant depression making it a treatment to consider in treatment resistant depression in anorexia though only case reports exist.